Contadora and the Central American peace process: selected documents - Bagley, Bruce Michael (Westview P. BoulderUS, 1985)
Attempts to shed light on the crucial roles of the Contadora Group (Colombia, Mexico, Panama and Venezuela) in forging peace in the region. Contains a collection of nearly one hundred statements, declarations, proposals, resolutions, draft treaties and official documents.